Internal auditing within the framework of Costa Rican private enterprises (National Administration Journal, 2021)
Internal and external auditing, internal control, risk management and corporate governance have evolved in the search for better strategies that contribute efficiently to the achievement of organizational objectives. This research analyzes the internal auditing unit in private Costa Rican enterprises. This study consists of a quantitative review of the following criteria: governing regulations, internal control, business risk management and corporate governance. The objective is to determine the perception of the business sector at the national level regarding the need to count on an internal auditor.
Keywords: Internal auditing; Risk management; Internal control; Corporative government